HbA1c Identifies Subjects With Prediabetes and Subclinical Left Ventricular Diastolic Dysfunction - Di Pino, Antonino; Mangiafico, Sarah; Urbano, Francesca; Scicali, Roberto; Scandura, Salvatore; D’Agate, Veronica; Piro, Salvatore; Tamburino, Corrado; Purrello, Francesco; Rabuazzo, Agata Maria (The journal of clinical endocrinology and metabolism, 2017)
ContextPrediabetes is associated with subclinical cardiac changes associated with heart failure development.ObjectiveWe investigated diastolic function and its association with markers of glycation and inflammation related to cardiovascular disease in patients with prediabetes. We focused on individuals with prediabetes identified only by glycated hemoglobin A1c [HbA1c; 5.7% to 6.4% and normal fasting glucose (NFG) and normal glucose tolerance (NGT) after an oral glucose tolerance test (OGTT)].DesignCross-sectional study.SettingDepartments of Clinical and Experimental Medicine and Cardiology, University of Catania, Catania, Italy.Main Outcome MeasuresHbA1c, OGTT, Doppler echocardiography, soluble receptor for advanced glycation end products (sRAGEs), and endogenous secretory RAGE (esRAGE) were evaluated.PatientsWe recruited 167 subjects with NFG/NGT who were stratified according to HbA1c level: controls (HbA1c <5.7%) and HbA1c prediabetes (HbA1c 5.7% to 6.4%).ResultsPatients with HbA1c prediabetes (n = 106) showed a lower peak mitral inflow in early diastole (E wave) to late diastolic atrial filling velocity (A wave) ratio (E/A ratio) than controls (n = 61) (1.10 ± 0.24 vs 1.18 ± 0.23; P < 0.05). They showed a higher left atrium volume (LAV) (28.4 ± 5 vs 22.1 ± 3; P < 0.05) and sphericity index (SI) (0.6 ± 0.06 vs 0.5 ± 0.05; P < 0.05). After multiple regression analyses, HbA1c, sRAGE, and esRAGE were the major determinants of E/A ratio, LAV, and SI.ConclusionsSubjects with HbA1c prediabetes exhibited subclinical cardiac alterations associated with sRAGE, esRAGE, and HbA1c. These subjects would not have been classified as having prediabetes on the basis of fasting glycemia or post-OGTT values.This study demonstrated the ability of HbA1c to identify subjects with prediabetes and subclinical alterations of diastolic function that would not have been detected using fasting glucose or OGTT.